Selective laser melting fabrication of functionally graded macro-porous Ti-6Al-4V scaffold for cavity bone defect reconstruction - Li, Zhuangzhuang; Luo, Yi; Liu, Ruicheng; Zou, Shanfang; Wang, Yitian; Gong, Taojun; He, Xuanhong; Zhou, Yong; Lu, Minxun; Min, Li; Tu, Chongqi (Frontiers in Bioengineering and Biotechnology, 2025)
Reconstruction of cavitary bone defects poses significant challenges in orthopedic surgery due to the irregular shapes and compromised mechanical properties of surrounding bone. This study developed a functionally graded macro-porous scaffold (FGMPS) using selective laser melting (SLM) for cavitary bone defect reconstruction. The FGMPS featured a porosity gradient (74%–86%) and macropores ≥1,600 µm, mimicking the natural density gradient of cancellous bone. Micro-CT analysis confirmed high structural fidelity and interconnected porosity. Compression tests in two orientations revealed distinct stress-strain responses: vertically aligned gradients (FGMPS-V) exhibited sequential layer engagement, while horizontally aligned gradients (FGMPS-H) demonstrated higher stiffness and strength due to uniform load distribution. The elastic modulus ranged from 383 MPa (FGMPS-V) to 577 MPa (FGMPS-H), with yield strength of 22–40 MPa, aligning well with cancellous bone properties. These findings highlight the FGMPS’s potential to offer a promising solution for cavitary bone defect repair.